Changes in organic acid and sugars levels during ripening of five loquat (Eriobotrya japonica Lindl.) cultivars - Serrano M.; Zapata P.; Pretel M.T.; Almansa M.S.; Botella M.A.; Amorós A. (First international symposium on loquat, 2003)
Changes in colour and sugar and organic acid content were analysed in five loquat cultivars. Colour changes occurred when loquat fruits were in a phase of fast growth, and concomitantly with both, the decrease in organic acid content and the increase in sugar levels. In the five loquat cultivars malic acid was the prominent organic acid in Algerie cultivar having a significantly higher content at fruit ripening than in the other loquat cultivars. Glucose, fructose and sucrose increased sharply during loquat ripening, while sorbitol concentration was high in young fruits and decreased quickly in the first weeks of fruit development. At commercial ripening stage sugar content was higher in Cardona, Golden and Peluche cultivars than in Magdall and Algerie.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)